Peran Kepemimpinan Kepala Sekolah dalam Penerapan Manajemen Strategi di SMK Gondang Wonopringgo Pekalongan - Ratnasari, Tria; Rokhmah, Asnalia (Jurnal Simki Pedagogia, 2026)
This study examines the role of leadership in the implementation of strategic management at SMK Gondang and identifies the leadership styles employed by the school principal in this process. A qualitative research design with a case study approach was adopted. Data were collected through in-depth interviews with school leaders, teachers, and administrative staff, as well as through direct observation of leadership practices and strategic management implementation at SMK Gondang. Data analysis followed the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the principal’s leadership plays a crucial role in decision-making and problem-solving related to strategic management implementation. Leadership is a key determinant in shaping the direction and ensuring the successful implementation of strategic management in vocational high schools. Furthermore, the principal at SMK Gondang demonstrates participative, transactional, and adaptive leadership styles, applying different approaches according to situational demands.